2016
DOI: 10.1074/jbc.m116.752782
|View full text |Cite
|
Sign up to set email alerts
|

The Salmonella Effector SpvD Is a Cysteine Hydrolase with a Serovar-specific Polymorphism Influencing Catalytic Activity, Suppression of Immune Responses, and Bacterial Virulence

Abstract: Many bacterial pathogens secrete virulence (effector) proteins that interfere with immune signaling in their host. SpvD is a Salmonella enterica effector protein that we previously demonstrated to negatively regulate the NF-κB signaling pathway and promote virulence of S. enterica serovar Typhimurium in mice. To shed light on the mechanistic basis for these observations, we determined the crystal structure of SpvD and show that it adopts a papain-like fold with a characteristic cysteine-histidine-aspartate cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…Typhimurium T3SS-effector proteins that have been previously shown to have the capacity to modulate this signaling pathway. Expression of spvD , which encodes a cysteine protease that has been reported to negatively regulate nuclear transport of NF-κB components [ 32 , 33 ], did not affect the ability of S . Typhi to stimulate NF-κB signaling ( Fig 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…Typhimurium T3SS-effector proteins that have been previously shown to have the capacity to modulate this signaling pathway. Expression of spvD , which encodes a cysteine protease that has been reported to negatively regulate nuclear transport of NF-κB components [ 32 , 33 ], did not affect the ability of S . Typhi to stimulate NF-κB signaling ( Fig 4B ).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, SpvB has been characterized as an (ADP-ribosyl)transferase, activating host cell actin degradation and thereby mediating cytotoxicity in macrophages and virulence in mice (Mazurkiewicz et al 2008), while SpvC was found to exhibit phosphothreonine lyase activity on host mitogen-activated protein kinases (MAPKs), leading to attenuation of the intestinal inflammatory response, which is thought to be important during systemic infection of S. typhimurium (Otto et al 2000). Recently, the function and crystal structure of the SpvD protein were elucidated and it was found that SpvD acts as a cysteine protease, which downregulates proinflammatory responses by indirectly inhibiting NF-kB regulated promoters and by doing so contributes to the systemic growth of S. typhimurium in mice (Grabe et al 2016;Rolhion et al 2016). In contrast, little is known about the SpvA protein and it is yet unclear if it is involved in Salmonella virulence (Roudier et al 1992;Rotger and Casadesus 1999).…”
mentioning
confidence: 99%
“…1 B ). The crystal structure and mutational analysis of SpvD suggest that SpvD is a cysteine protease; however, exactly how this protease function negatively regulates NF-κB signal transduction is still unknown ( Grabe et al, 2016 ). Overall, many intracellular bacterial pathogens secrete effectors that target MAPK and NF-κB signaling pathways to counteract the deleterious output of these host defense pathways and prevent downstream proinflammatory cytokine expression.…”
Section: Bacterial Inhibition Of Innate Immunitymentioning
confidence: 99%